2020
DOI: 10.1111/are.14949
|View full text |Cite
|
Sign up to set email alerts
|

The use of probiotics in larval whiteleg shrimp ( Litopenaeus vannamei ) production: A marginal analysis of bioeconomic feasibility

Abstract: Sustainable production in aquaculture requires integrating new technologies that maximize economic benefits while minimizing environmental impacts. In shrimp production, probiotics improve larval survival and reduce environmental impacts, but their use also increases total production costs. In this study, the economic feasibility of using probiotics in larval whiteleg shrimp production was assessed, as well as the optimal concentration to maximize the economic performance of a laboratory for larval whiteleg sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The gradual and progressive resistance that various farm animals have to antibiotics represents a critical and serious global threat to human health due to the use and abuse of these chemotherapeutic agents in producing aquatic food (Hasan et al 2020). Probiotics offer several biological benefits; they reduce the proliferation of pathogenic bacteria through competitive exclusion (Zorriehzahra et al 2016) and improve survival (Peñalosa-Martinell et al 2021). Probiotic bacteria are supplied live and can colonize the digestive tract, modify intestinal microbiota, and improve the immune response (Hoseinifar et al 2018).…”
Section: ____________________mentioning
confidence: 99%
“…The gradual and progressive resistance that various farm animals have to antibiotics represents a critical and serious global threat to human health due to the use and abuse of these chemotherapeutic agents in producing aquatic food (Hasan et al 2020). Probiotics offer several biological benefits; they reduce the proliferation of pathogenic bacteria through competitive exclusion (Zorriehzahra et al 2016) and improve survival (Peñalosa-Martinell et al 2021). Probiotic bacteria are supplied live and can colonize the digestive tract, modify intestinal microbiota, and improve the immune response (Hoseinifar et al 2018).…”
Section: ____________________mentioning
confidence: 99%
“…A Probiotic application in larval whiteleg shrimp (L. vannamei) resulted in a 6% increase in total production costs. However, the result of a higher survival rate contributed to a 44% reduction in unit production costs [297]. Studies on the feasibility of synbiotics in aquaculture have consistently shown improvement in economic efficiency compared with control diets, especially when aquatic animals have been under stress conditions such as high stocking density [298] or during the reproductive period [299].…”
Section: Limitations Of the Use Of Synbiotic Agents In Aquaculturementioning
confidence: 99%
“…From the perspective of aquaculture, probiotics can be administered directly to the rearing water or supplemented in feed. These adjuncts potentially induce beneficial effects on animal health through the direct modulation of host‐associated factors or via the indirect enhancement of the ambient environment quality 67,68 (see Section 2.3).…”
Section: Bacterial‐derived Additivesmentioning
confidence: 99%
“…vannamei larvae, 44% reduction in the unit production cost was accompanied by 6% increment in the total production expenses. The profitability greatly relied on the financial capability of the farm to sustain the investment throughout the production cycles 67 . Since the financial consideration is one key factor limiting the large‐scale implementation, besides studying the efficacy of the additive, comparing the economic sustainability with other available strategies is necessary 246 .…”
Section: Future Research Perspectivesmentioning
confidence: 99%